Hubungan Tingkat Pengetahuan dengan Perilaku Perawat Dalam Pemberian Nutrisi Enteral pada Pasien Kritis di Ruang ICU - Hana Ningtias; Maryana; Aan Devianto (LPPM STIKES NOTOKUSUMO YOGYAKARTA, 2015)
Background: Most of the time, critically ill patients admitted to the critical care rooms of ICU (Intensive Care Unit) suffer from lack of nutrient intake. The significance of nutrient, particularly for critically ill patients, demands clinicians to obtain reliable information on the factors contributing to the management of administering nutrient and the influence of administering adequate amount of nutrient upon the outcome of critically ill patients in ICU. Objective: This study aims to reveal the correlation between nurses’ knowledge and their behavior in administering enteral nutrient to critically ill patients. Method: This study is a cross-sectional study analyzing the correlation between nurses’ knowledge and behavior in administering enteral nutrient. Samples were derived from 19 respondent taken at the ICU rooms of JIH Hospital. Chi Square test is employed to reveal the correlation between nurses’ knowledge and behavior with a standard error of 5% (0.05). Result: The findings reveal that in terms of nurses’ level of knowledge in ICU rooms of JIH,2 respondents are under Good category (10,5%) and 17 respondents are under Mediocre category (89,5%). In terms of nurses’ behavior in administering enteral nutrient to critically ill patients, 13 respondents are identified under Good category (68,4%) and 6 respondents are under Poor category (31,6%). The bivariate analysis results in a p value at 0,032. Conclusion:There is a significant correlation between nurses’ knowledge level and their behavior in administering enteral nutrient to critically ill patients in ICU of Jogja International Hospital of Yogyakarta.